Incidencia del gobierno electrónico en la gestión pública del gad municipal del cantón Quevedo año 2022 - Victorero Veas, Adriana Lorena (2023)
The essential element of the research was to establish the importance of public management for a citizen approach to social impact, the main problem being the limited access to information and public service of the citizens of Quevedo, for which the main objective was to evaluate The Impact of electronic government on the public management of the Municipal GAD of the Quevedo canton, 2022. The research was descriptive, applying the inductive and deductive method. The study population was made up of the main authority of the Municipal GAD (mayor), the ICT coordinator, the ICT department staff and external users (citizens); For the latter, sampling is necessary, which determined a sample of 384 users. To collect information, interview and survey techniques were applied. The main results showed that there is little evaluation of the effectiveness of the services, resistance to change prevails within the ICT department; and on the other hand, according to external users, 45% stated that when using the municipality's digital platforms their experience has been positive. Since it is concluded that the implementation of electronic government has had some success in facilitating access to public services, as well as that the use of electronic government improves the operational efficiency and accessibility of public services, therefore through the interaction through the web portal, citizen participation can be promoted.